Policing, social media and the new media landscape: can the police and the traditional media ever successfully bypass each other? - Colbran, Marianne P. (Policing and society, 2020)
This study explores three issues. Firstly, it examines the effect of the use of digital platforms on the relationship between the police, the press and the public, in the context of restricted police/press contact in the United Kingdom. Secondly, it considers the question, raised in an Australian context (Lee, M. and McGovern, A., 2014. Policing and media: public relations, simulacrums and communications. Abingdon and New York, NY: Routledge), as to whether the use of digital platforms allows the police, or more specifically in this study, the Metropolitan Police Service (MPS), to bypass the national British news media. Lastly, it identifies convergences and divergences with Lee and McGovern’s study of police and press relations. Lee and McGovern’s study indicates that, while the use of digital platforms has increased police control over flow of information, there is still a symbiotic police/press relationship. This study finds that, while the use of digital platforms has appeared to increase police transparency, the reverse is the case, and that the use of digital platforms has given the MPS more control than ever before over the flow of information to the press. The study suggests that these developments have serious consequences for the integrity of crime reporting and for democratic practices in the United Kingdom.